Itinerant School Herdeiros do Saber: an analysis on the process of transforming the "School of Teaching" to the "School of Work" - Rose Riepe de Souza; Clésio Antonio Acilino (Universidade Federal do Norte do Tocantins, 2021)
The article presents a research that has as object of study the Itinerant School Herdeiros do Saber of the Landless Workers Movement, Rio Bonito do Iguaçu, Paraná. The objective of the research was to analyze the process of transforming the pedagogical practices of the "School of teaching" to the "School of work", from the perspectives of the teachers working in that school. The case study methodology used semi-structured interviews, participant observation and field diary. The research seeks to contribute to the discussions about the school form in the movement of pedagogical transformations of rural schools. The research results show a process of construction of pedagogical practices guided by work as an educational principle, the link between school education and life and the school organization, with different times and spaces. In these areas, the main contradictions present express questions of the centrality of teaching scientific knowledge, of pedagogical and school management practices, of the training of teachers. Finally, it presents some challenges of the school experience analyzed regarding the consolidation of the school's pedagogical proposal, the lack of resources and investment and the political context of the school's social reality.